Description of a Comprehensive Medication Management service in an adult intensive care unit - Igor G. SOUZA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objective: To describe the results of a Comprehensive Medication Management (CMM) service offered to patients of an adult intensive care unit. Methods: A descriptive cross-sectional study of the results of the CMM service (April 2017 to November 2018). All the patients followed up in the CMM service were included in the sample of this study. The service was integrally based on the Pharmaceutical Care Practice and, therefore, used the Pharmacotherapy Workup (PW) method. the drug therapy Problems (DTP) were quantified and classified according to the PW method. The main medications involved in the DTP were also described, as well as the acceptance of the interventions by the multidisciplinary care team members and patients. Results: 146 patients were followed up during the study period, and 512 DTP were identified. Of these DTP, most were related to medication safety (37.7%) and to indication (37.5%). The main causes were high dose (23.0%, with emphasis on dose adjustments in cases of kidney injury), need for additional medication (18.9%, inclusion of medication for electrolytic, glycemic, and prophylactic control), and unnecessary medication (18.6%, emphasis on de-prescription of antibiotics that were not indicated). Most of the problems (23.6%) were related to the therapeutic class of systemic anti-infective agent. Of the total DTP detected, 81.6% were resolved. A total of 451 interventions were implemented, of which 92.9% (n=419) were with physicians. The majority of the interventions with physicians were accepted (n=344, 82.1%). Conclusion: A high number of drug therapy problems have been detected and resolved by the CMM pharmacist, with emphasis on safety problems. The high acceptability of the interventions reinforces the need for the service applied to the critical patient.